What about the Portuguese oldest old? A global overview using census data - Brandão, Daniela (2019)
Background The older population is itself aging, and achieving an advanced age is becoming more common worldwide. In Portugal, individuals aged 80+ represent 5.6 % of the total population and 26.5 % of the popu- lation were aged 65 and over in 2011. Having a national profile on this population will give important information to develop interven- tion programs and identify the areas requiring most attention. Ob- jective: This study aims to provide a profile of the Portuguese oldest old, as given by the last national census data. Methods The characteristics of all residents aged 80+ (N = 532,219) were ana- lysed considering socio-demographic information (gender, marital status, education, type of residence, place of birth, income) and the existence of difficulties in functional, sensorial and cognitive activities due to health problems or ageing. Results The majority of the most aged are females (64.5 %), widowed (53.9 %), and present low educational levels (46.1 % never attended school and 31.6 % do not know how to read/write). Own pensions constitute the main source of income (96.3 %) and the majority live in private households (88.8 %), with 43.2 % currently living in the place where they were born. The majority (73.0 %) reported major difficulties in at least one functional activity – bathing/dressing, walk- ing/climbing stairs, seeing, hearing, memory/concentration, under- standing others/being understood. Conclusions The high percentage of oldest old living in private households and the presence of functional limitations point to the importance of in- formal care and community care services to support this population. Further studies paying attention to their needs and utilisation of ser- vices are required.